Non-traumatic subarachnoid hemorrhage due to ruptured middle cerebral artery aneurysm in a young lady: a challenge in diagnosis - Mohammad Sallehuddin, Hakimah; Hoo, Fan Kee; Tan, Yi Jun (Pakistan Medical Association Rawalpindi Islamabad Branch, 2016)
We present a case of a young lady who had subarachnoid hemorrhage and was initially misdiagnosed as acute sinusitis. High index of suspicion and ability to analyze her risk factors and associated electrocardiographic, biochemical and radiological findings eventually led to the right diagnosis and treatment. A high index of suspicion remains the cornerstone of diagnosis.